The second to fourth digit ratio in elite and non-elite Greco-Roman wrestlers - Keshavarz, M.; Bayati, M.; Farzad, B.; Dakhili, A.; Agha-Alinejad, H. (Journal of Human Kinetics, 2017)
A low second-to-fourth digit ratio (2D:4D) has been reported to correlate with high performance and athletic potential of an individual in sport. It has been suggested that 2D:4D is a relatively weak predictor of strength and a stronger predictor of efficiency in aerobic exercise. Comparing extreme groups on a continuum of sports performance requiring high power (physical strength) output would be helpful to resolve this issue. Therefore, the purpose of the present study was to compare the 2D:4D ratio of world-class elite Greco-Roman wrestlers (n = 10) taking part in Olympic fitness camps in 2013 with the 2D:4D ratio of non-elite collegiate wrestlers (n = 20), and age-matched sedentary males (n = 40). The 2D:4D ratios of elite wrestlers were lower compared to non-elite athletes (p < 0.01, right hand d = 1.70, left hand d = 1.67) and the control group (p < 0.0001, right hand d = 3.16, left hand d = 2.00). No significant differences were noted among the groups for right - left 2D:4D. We concluded that 2D:4D may discriminate between non-elite and world-class wrestlers. We also suggest that a low 2D:4D ratio could be linked to performance potential in wrestlers. As such, 2D:4D may provide additional information, which is valuable in determining the potential athleticism of an individual, when it is used in conjunction with other measures.